Mix Design of Geopolymer No-fines Concrete with Fly Ash and Ground Granulated Blast Furnace Slag - Yuhasnita, Angeline; Siswosukarto, Suprapto; Satyarno, Iman (Universitas Negeri Yogyakarta, 2024)
The use of geopolymers as a cement replacement in no-fines concrete can be a solution to address the impact of cement production on global warming. The absence of standardized mix designs for geopolymer paste poses a challenge, particularly concerning workability in no-fines geopolymer concrete mixes, where insufficient workability can hinder compacting, while excessive workability may cause segregation. Additionally, geopolymer often exhibits a quick hardening time, necessitating the use of retarders such as borax. This study aims to evaluate the impact of varying the ratio of alkali activator to cementitious material (A) at 0.25, 0.30, and 0.35, with the addition of borax (C) at 3% and 5%, on the flow and hardening time of geopolymer paste. Additionally, the study aims to investigate the effect of the cement-to-aggregate volume ratio (P) on geopolymer no-fines concrete properties, particularly compressive strength and unit weight. In no-fines geopolymer concrete formulation, the absolute volume of geopolymer paste is equivalent to the volume of cement paste with a 0.4 water-to-cement (w/c) ratio, with a cement-to-aggregate volume ratio of 1:4 and 1:6. The geopolymer mixture consists of fly ash and GGBFS in a 50:50 ratio. The geopolymer activator consist of NaOH (10 M) and Na2SiO3 in a SS/SH (R) ratio of 2. The research results indicate that reducing the A ratio from 0.35 to 0.25 decreases flow and accelerates the hardening time of the geopolymer paste. Increasing the borax (C) content from 3% to 5% can prolong the hardening time and reduce flow (from 20.25 to 19.25 cm at an A ratio of 0.30). The test results of geopolymer no-fines concrete properties that increasing the volume ratio (P) from 1:4 to 1:6 can reduce the compressive strength from 30.95 to 13.27 MPa and the unit weight from 2158.83 to 1843.38 kg/m³ at (A) 0.35. However, in the concrete samples at this ratio, some voids were covered by paste. Therefore, it is recommended to use ratio (A) 0.30.